Guselkumab in Patients with Scalp Psoriasis: A post hoc Analysis of the VOYAGE 2 Phase III Randomized Clinical Trial - Enikö Sonkoly; Julia-Tatjana Maul; Matteo Megna; Patricia Gorecki; Edmée Crombag; Jozefien Buyze; Laura Savage (Medical Journals Sweden, 2024)
Scalp psoriasis affects approximately 80% of patients with psoriasis and can negatively impact their quality of life. This post hoc analysis of the VOYAGE 2 Phase III randomized clinical trial evaluated scalp response to guselkumab treatment and its association with skin response and patient-reported outcomes. The study included patients with moderate-to-severe plaque psoriasis and baseline scalp psoriasis who were initially randomized to receive guselkumab. Patients were divided into 3 groups based on their achievement of a Psoriasis Area and Severity Index 90 response at week 28: responder continuation, non-responder continuation and responder withdrawal. In all 3 groups, mean Psoriasis Area and Severity Index head and scalp-specific Investigator's Global Assessment scores improved through week 28. In the responder withdrawal group, these scores worsened after treatment withdrawal at week 28, but remained stable through week 48 in both continuation groups. Trends in Dermatology Life Quality Index and Psoriasis Symptoms and Signs Diary itch scores mirrored those of mean scalp-specific Investigator's Global Assessment scores through week 48. Within-subject correlations were 0.83 between scalp-specific Investigator's Global Assessment and Psoriasis Area and Severity Index head scores and 0.78 between scalp-specific Investigator's Global Assessment and Psoriasis Symptoms and Signs Diary itch scores. Through week 252, Psoriasis Area and Severity Index head scores remained stable in the responder continuation group, improved in the non-responder continuation group and rapidly improved by week 84 in the responder withdrawal group after retreatment.